2001
DOI: 10.1161/01.atv.21.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NO Synthase Overexpression Inhibits Lesion Formation in Mouse Model of Vascular Remodeling

Abstract: Abstract-NO produced by endothelial NO synthase (eNOS) plays important roles in the regulation of vascular tone and structure. The purpose of this study was to clarify the role of eNOS-derived NO on vascular remodeling by use of eNOS-transgenic (eNOS-Tg) mice. The common carotid artery was ligated just proximal to the carotid bifurcation. Four weeks later, the proximal carotid artery of the ligation site was histologically examined. In this vascular remodeling model, the endothelium remains uninjured, but neoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 42 publications
2
80
0
Order By: Relevance
“…Beginning at 22 weeks, mice common carotid artery lesions 17,18 were induced by ligation of the left common carotid artery. At 28 days after surgery, the experimental animals were euthanized to evaluate carotid artery neointimal formation.…”
Section: Mouse Common Carotid Ligation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning at 22 weeks, mice common carotid artery lesions 17,18 were induced by ligation of the left common carotid artery. At 28 days after surgery, the experimental animals were euthanized to evaluate carotid artery neointimal formation.…”
Section: Mouse Common Carotid Ligation Modelmentioning
confidence: 99%
“…Although our present studies demonstrated that carotid ligation induced a significant neointimal formation in DIO mice, we did not observe neointimal formation in control mice as other investigator reported. 17,18 Different mouse strain and genetic background have been shown to have a significant different in the neointimal formation in carotid ligation model. 45,46 Whether these factors contribute to this discrepancy in present studies remains unknown.…”
Section: Disscussionmentioning
confidence: 99%
“…NO produced by eNOS possesses anti-inflammatory, antiatherogenic, and anti-ischemic properties [71,72]. Enhanced NO production by administration of the eNOS substrate Larginine or upregulation of eNOS by statins confers stroke protection [73,74,75], and transgenic mice overexpressing eNOS show decreased leukocyte accumulation and reduced vascular lesion formation following vascular injury [76]. Conversely, mice with targeted disruption of eNOS (eNOS −/− ) exhibit increased vascular inflammation and larger cerebral infarctions following experimental ischemia [77,78], while inhibition of NOS activity decreases cerebral blood flow and increases infarct size after ischemia [79].…”
Section: Nontranscriptional Activation Of Enos By Corticosteroidsmentioning
confidence: 99%
“…VSMCs primarily regulate vascular tone and contraction and are important in the medial layer of arteries. In animal models of vascular injury, intimal and medial thickening is attributed to phenotypic switching of resident VSMCs and their proliferation and migration from the adventitia and media to the intimal space (Janssens et al, 1998;Kawashima et al, 2001;von der Thusen et al, 2004). Therefore, augmentation of neointimal formation in iatrogenic response to therapeutic intervention compromises flow and www.intechopen.com increases the risk of a cardiac event.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of cGMP signaling are not well understood, since studies suggest that NO can both promote and inhibit pathological vascular remodeling (Kawashima et al, 2001;Ozaki et al, 2002;Rudic et al, 1998). Furthermore, recent studies provide sound evidence for NO-independent heme oxygenase (HO) and carbon monoxide (CO) as physiologically relevant signals capable of activating sGC and promoting cGMP signal transduction (Christodoulides et al, 1995;Siow et al, 1999;Tulis et al, 2001a;Tulis et al, 2001b;Tulis et al, 2005).…”
mentioning
confidence: 99%